2021
DOI: 10.3390/jof7090683
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, Structural Characterisation, and Immunomodulatory Properties of Edible Amanita hemibapha subspecies javanica (Corner and Bas) Mucilage Polysaccharide as a Potential of Functional Food

Abstract: This research aimed to extract mucilage polysaccharides (MP) from Amanita hemibapha subspecies javanica (Corner and Bas), and further fractionate them using anion-exchange chromatography, yielding two fractions (MPF1 and MPF2). The crude extract, and fractions mainly consisted of carbohydrates (83.5–93.2%) with minor amounts of proteins (5.40–7.20%), and sulphates (1.40–9.30%). Determination of the monosaccharide composition revealed that glucose was the major unit, followed by galactose, mannose, rhamnose, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Nevertheless, in earlier research, polysaccharide from this mushroom escalated NO, IL-1β, IL-6, and TNF-α production [13], activated IL-1β, and IL-18 secretion in LPS-induced macrophages [14], and IL-1β, IL-6, and IL-18 were enhanced in colitis mice [43]. Recently published studies reported that the bioactive compounds from various sources could regulate the immune system [39,[44][45][46][47][48].…”
Section: Anti-inflammatory Activitymentioning
confidence: 88%
See 1 more Smart Citation
“…Nevertheless, in earlier research, polysaccharide from this mushroom escalated NO, IL-1β, IL-6, and TNF-α production [13], activated IL-1β, and IL-18 secretion in LPS-induced macrophages [14], and IL-1β, IL-6, and IL-18 were enhanced in colitis mice [43]. Recently published studies reported that the bioactive compounds from various sources could regulate the immune system [39,[44][45][46][47][48].…”
Section: Anti-inflammatory Activitymentioning
confidence: 88%
“…Nevertheless, in earlier research, polysaccharide from this mushroom escalated NO, IL-1β, IL-6, and TNF-α production [13], activated IL-1β, and IL-18 secretion in LPS-induced macrophages [14], and IL-1β, IL-6, and IL-18 were enhanced in colitis mice [43]. Recently published studies reported that the bioactive compounds from various sources could regulate the immune system [39,[44][45][46][47][48]. This result agreed with a previous study, showing that crude polysaccharide from D. indusiata extracts could reduce inflammatory cytokines (IL-1β, IL-6, and TNF-α) in antibiotic-induced intestinal dysbiosis in mice [41].…”
Section: Anti-inflammatory Activitymentioning
confidence: 88%
“…( Phillips, 2010 ). There are some poisonous species, some lethally so, of Amanita such as Amanita farinose, Amanita brunnescens, Amanita pantherina, Amanita cokeri, Amanita ceciliae, Amanita crenulata, Amanita muscaria, Amanita porphyria, Amanita frostiana, etc., Amanita ocreata, Amanita smithiana, Amanita abrupta, Amanita subjunguillea, Amanita virosa, Amanita proxima, Amanita exitialis, Amanita arocheae, Amanita magnivelaris, Amanita bisporigera, Amanita phalloides, Amanita smithiana, and Amanita verna respectively ( Zeitlmayr, 1976 ; Surayot et al, 2021 ).…”
Section: Potential Medicinal Mushroomsmentioning
confidence: 99%
“…Polysaccharides, formed by α - or β -glycosidic bond of identical or various monosaccharide monomers with10 or more polymerization, are naturally produced in large quantities by plants and fungi ( Tan et al, 2017 ). To date, numerous polysaccharides have been shown to exhibit a range of biological activities, including anticoagulation, antiviral, antitumor, antioxidant, hypoglycemic, and immunomodulatory effects ( Zeng et al, 2019 ; Zhang et al, 2019 ; Wang et al, 2019b ; Kalinina et al, 2020 ; Chaisuwan et al, 2021 ; Chen C. et al, 2021 ; Kiddane and Kim, 2021 ; Liang Q. et al, 2021 ; Surayot et al, 2021 ; Figure 1 and Table 1 ). In addition, many studies have proposed that some polysaccharides also contribute to shaping the structure, diversity and function of gut microbiota and thus play a role in enhancing human health ( Koropatkin et al, 2012 ; Chang et al, 2015 ; Lin et al, 2018 ; Zhang L. et al, 2018 ; Zhang X. et al, 2018 ; Chen G. et al, 2019 ; Ding et al, 2019 ; Wang M. et al, 2019 ; Wang Y. et al, 2020 ; Wang et al, 2020b ; Guo et al, 2021a ).…”
Section: Introductionmentioning
confidence: 99%